Selma Garrido: in defense of public education and quality - Nonato, Claudia (2016)
With a life totally dedicated to education, Selma Garrido Pimenta is retired as Senior Professor at the Faculty of Education (FE- USP) and Assistant Professor in the Graduate Program in Education at the Catholic University of Santos. Coordinates the GEPEFE - Group of Studies and Research on Education Educator, with the Graduate Program in Education - FEUSP, and closely follows the recent changes in Brazilian education. In this interview, held in São Paulo, the teacher makes a detailed analysis of the National Curriculum Guidelines for Initial Training and Continuing of the Magisterium of the Basic Education Professionals, adopted in 2015; furthermore, it criticizes the privatization of public schools, teacher training, and the commodification of higher education in Brazil.